Trust me always - Brandy, Meagan (Brandy, Meagan, Boys of Avix, 2025)
Cameron Cox never planned to fake-date campus heartthrob Brady Lancaster--especially not while her ex, Alister Howl, fights to win her back. With secrets, second chances, and blurred lines between love and lies, she's caught in a game where someone's bound to get hurt.